American National Election Studies, 2000, 2002, and 2004: Full Panel Study ([Verlag nicht ermittelbar], 2009)
This data file does not represent new content, but instead it is the result of merging data from the 2000 NES, the 2002 NES, and the 2004 ANES Panel Study. The 2000 ANES contains questions in areas such as values and predispositions, media exposure, social altruism, and social networks. Special-interest and topical content includes a sizable battery on the Clinton legacy and a smaller retrospective battery on former President George H.W. Bush, new social trust questions specific to neighborhood and workplace, expanded content on civic engagement, questions related to the debate about campaign finance reform, and the first ANES time series appearance of measures on cognitive style. The 2002 ANES contains questions in areas such as social trust and civic engagement. Special-interest and topical content includes questions on the terrorist attacks of September 11, 2001, the war on terrorism, economic inequality, the 2000 Presidential election, recent corporate scandals, the 2001 tax cut, and proposed elimination of the estate tax. The 2004 phase of the panel study was given in large part to questions that capture the likely consequences of the election contest of 2000 and the terrorist attack of September 11th, as understood and interpreted by ordinary Americans. This included instrumentation on participation in political and civic life, satisfaction with democratic institutions, support for administration policy, and views on Afghanistan, Iraq, and homeland security. Demographic variables include sex, race, age, marital status, family income, education level, religious preference, political party affiliation, voter participation history, and registration status.